Dietary Capsaicin Supplementation Mitigates Calving-Induced Stress and Enhances Antioxidant Capacity, Immune Function, and Gut Microbiota in Periparturient Dairy Cows - Hangfan Li; Zibin Wu; Baisheng Yu; Jinyuan Chen; Chuang Yang; Yongqing Guo; Baoli Sun (Antioxidants)
This study investigated the effects of dietary capsaicin supplementation on antioxidant capacity, immune function, and gut microbiota in periparturient dairy cows. Twenty Holstein cows with an average parity of 2.5 ± 0.76, milk production of 31.30 ± 2.39 kg, and 36.10 ± 2.38 days to calving were randomly assigned to either a control group fed a basal diet or a treatment group supplemented with 1.2 g/head/day of capsaicin. The supplementation was administered during an evaluation period spanning from 28 days before delivery to 21 days after delivery using a randomized block experimental design. Results showed that capsaicin significantly reduced milk somatic cell count and pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6) while enhancing serum antioxidant enzymes (SOD, GSH-Px, and CAT) and immunoglobulin levels (IgG, IgA, and IgM). Moreover, capsaicin altered gut microbiota composition, increasing the relative abundance of beneficial genera. These findings suggest that dietary capsaicin supplementation during the transition period improves lactation performance and supports immune function, as well as alleviates oxidative stress. This study highlights the potential of capsaicin as a practical dietary strategy for enhancing productivity in dairy farming.